Clinical trials on healthy volunteers in Mumbai and Ahmedabad: expanding the framework of expropriation - Wadkar, Navneet A. (International Journal Of Community Medicine And Public Health, 2021)
Background: Healthy volunteers (HVs) in phase I clinical trials in India are often motivated by financial compensation. Historical expropriation and every day struggle for life of HVs which contributes to normalization of the risk are often ignored as contributing factors to normalization of risk. Therefore this research was aimed to study expropriation experiences of the HVs. Methods: This research has employed qualitative and exploratory research design. The purposive sampling method was used to recruit nine HVs from two cities Mumbai and Ahmedabad. Results: All of the HVs and their family members were alienated from land and livelihood in their villages through different social, economic, political and cultural processes. The financial compensation was a primary motivation and not altruism. The compensation amount was spent to pay debts, medical and other emergencies, consumer goods and alcohol. To maximize their earnings, HVs have participated in consecutive and/or more than one trial simultaneously. Conclusions: The serial participation of the HVs in phase I trials has exposed them to serious risks which they are unable to recognize unless severe adverse events (SAE) occurred. The existing scholarship suggests that the perceived risk by healthy volunteers normalized through attractive financial incentives and serial participation. But findings of this research indicate that state induced violence, caste, class, gender based violence and everyday struggle of survival are also major contributing factors.